A Feasibility study on Tropical Treasures - Baguio, Rey Gabriel (College of Engineering, 2005)
The feasibility of Tropical Treasures Coconut Flour as a partial substitute for wheat flour was evaluated in the this study. Coconut flour is a low cost and high-protein, low fat alternative to other kinds of flours. Coconut flour can be made from different forms of the coconut meat. It may be made from pared or unpared meat, dehydrated or not. The overall feasibility of Tropical Treasures Coconut Flour was segmented into three main aspects namely, market, technical and financial. In the market study, analysis of the demand and supply of wheat flour in the country was studied. The bakery product industry which makes up 71% of the flour market will be the target market of coconut flour. its low cost and nutritional benefits would be its competitive advantage against other flours. With the analysis of the marketing mix, it was realized that Tropical Treasures Coconut Flour has a potential in entering the commercial market. For the technical study, operational process procedures, materials, equipment, facility and organizational design were the focus of analysis. The overall production and operational details for the product were established and conclusions on technical feasibility were drawn. The financial study included estimating overall project start-up cost and how to finance it. The initial investment was found to be P7 million. Pro-forma financial statement for the first five years was also projected. Analysis of the statements yielded positive results. Additionally the organizational and management structure of the company and corresponding compensation was developed. Lastly, a social profitability analysis was also conducted which identified the overall benefits and costs of the product to society and the nation. A net benefit valued at Php52 million was projected contribution to the economy and society for the initial 5-year operation of Tropical Treasures coconut Flour production. Overall, Tropical Treasures Coconut Flour is a viable product when marketed as a partial substitute to wheat flour.